Habitat Analysis and Study on Threats to Chinese Pangolin (Manis pentadactyla) in Patletar Patle Community Forest, Bhaktapur - Dulal, Sujan; Ghimire , Bina; Regmi, Praveen Kumar (NUTA Journal, 2024)
Pangolin is a scaly anteater, nocturnal, elusive, non-aggressive, solitary, burrowing strange mammals found in the different parts of Nepal and is listed as a critically endangered species in IUCN Red List. The research was carried out in the Patletar Patle community forest of Bhaktapur District in Central Nepal to identify the status of burrows, threat analysis and to assess the perception of local people towards pangolin. The direct field observation has been carried out May 27 to June 7 2019 to know the status of burrows and the semi- structured questionnaire survey has been prepared to access the perception of local people and the threats has been analyzed. Also the secondary data from the literature review were analyzed. Altogether 36 burrows (27 old and 9 new) were recorded during the survey. The distribution of the burrows was found to be uniform throughout the transects. Burrows were mostly present in the elevation range of 1375-1400 m and all the burrows were present in the northeast slope aspect. The burrows were mostly located in the acidic soil type and were located in slope aspect. The people of the area lack scientific knowledge towards the pangolin but possessed positive perception towards it. Out of 33 respondents only 1 % of respondents have seen the pangolin. The people argued that the none encounter was made by the pangolin towards human, but some of them, argued with rarely encounter and the sometime encounter. The study area lies nearer to the Suryavinayak Community Forest. So, the people thought that the reason behind the presence of Pangolin is due to the migration of pangolin from Suryavinayak Community Forest. However, intensive study is needed in the study area which could be imperative for the conservation of the species.